2011
DOI: 10.3389/fpsyg.2011.00335
|View full text |Cite
|
Sign up to set email alerts
|

Reward and punishment effects on error processing and conflict control

Abstract: Recently, positive affect has been reported to reduce cognitive conflicts and adaptations related to conflict control. van Steenbergen et al. (2009) proposed that the aversive quality of conflicts drives short-term adaptations following a conflict. They reasoned that monetary gain and its positive emotional consequences might counteract the aversive quality of conflict and hence reduce subsequent adaptations. In two experiments, we combined Simon-type conflicts with monetary gains and losses in between trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
116
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 45 publications
15
116
2
Order By: Relevance
“…Second, the affective stimulus might act as a reward or punishment signal related to the previous trial (e.g., Braem, Verguts, Roggeman, & Notebaert, 2012;Stürmer, Nigbur, Schacht, & Sommer, 2011). Because it is difficult to distinguish whether the modulation of conflict adaptation in these studies was driven by the affective or motivational aspect of the inserted stimuli, we prefer to use the method of sustained mood induction to investigate emotional influence on conflict adaptation.…”
Section: Emotional Modulation Of Conflict Adaptationmentioning
confidence: 99%
“…Second, the affective stimulus might act as a reward or punishment signal related to the previous trial (e.g., Braem, Verguts, Roggeman, & Notebaert, 2012;Stürmer, Nigbur, Schacht, & Sommer, 2011). Because it is difficult to distinguish whether the modulation of conflict adaptation in these studies was driven by the affective or motivational aspect of the inserted stimuli, we prefer to use the method of sustained mood induction to investigate emotional influence on conflict adaptation.…”
Section: Emotional Modulation Of Conflict Adaptationmentioning
confidence: 99%
“…Indeed, increased top-down control is implemented if performance is incentivised or punished (Chiew & Braver, 2013;Riesel et al, 2012;Saunders et al, 2015a;Stürmer et al, 2011), when threatening images signal the need to inhibit a pre-potent response (Senderecka, 2016), after negative mood inductions (Kuhbandner & Zehetleitner, 2011; Affective neuroscience accounts of control also predict that awareness of internally generated emotional states should moderate control. Alexithymia reflects individual differences in the ability to detect and describe self-generated emotion (Taylor, Bagby, & Parker, 1999).…”
Section: The Emotive Nature Of Conflict and Control Implementationmentioning
confidence: 99%
“…Furthermore, though reward and punishment have been found to share the same brain region, namely the cingulate cortex which is critically involved in processing the expectation and occurrence of reward and punishment (Stürmer, Nigbur, Schacht, & Sommer, 2011), they have rarely been studied simultaneously, which may be probably due to their opposite affective value. For example, Krebs, Boehler, and Woldorff (2010) mainly investigated how reward associations influenced the processing of conflicting information with monetary incentives, and they found that color-naming performance in a Stroop task was enhanced on trials with potential-reward versus those without.…”
mentioning
confidence: 99%